Franchising - Iberian companies internationalization - Pedro, Maria Isabel (2013)
A study has been made for the internationalization of the franchising Iberian companies. Our aim was to analyze the most important variables for the internationalization. We studied it using several statistical methods applied to the answers given by companies to a questionnaire. We have concluded that are some relevant variables to be considered in the internationalization such as age, dimension, bond, dispersion, structure of the network and some variable connected with environment and motivational factors.